What does development mean today? Rewriting the socio-economic Paradigm - Ghosh, Jayati (Social Scientist)
In this paper I intend to discuss some of the central concerns that have emerged at least for me about development in recent times. I will try to cover three very broad questions. How has our vision of development changed since the heyday economics(3y (BHow do we measure progress today and how should we be measuring it? And finally, where do we go from here?- Reproduced s